Prediction of the Erosion and Sedimentation Rate Using SWAT Model in Keduang Sub-Watershed Wonogiri Regency - Nugroho, Prima; Priyana, Yuli; Haryadi, Sigit (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2015)
Increased rate of erosion and sedimentation undeniably will bring degradation to the affected area, particularly in the watershed ecosystem. This problem, however, can be reduced by applying a proper watershed management, especially in the upstream. Watershed management would be carried out based on analysis of the watershed performance. A hydrological modelfrequently used to determine the impact of the landuse and physical environmental conditions onthe rate of erosion and sedimentation spatially and temporally is Soil Water Assessment Tool(SWAT), This research aimed: (1) to determine the accuracy of the monthly model simulationand, (2) to analyze the rate of erosion and sedimentation in Keduang sub-watershed. The statistical method used to test the model was Nash-Sutcliffe efficiency (NS) and the coefficient of determination. Result of model validation obtained value of R2 = 0.79 and NS = 0.41. The area with a high erosion rate was as much as 17,950.75 ha (51.22%) and very high erosion rate was 7,771.25 ha (22.17%). Average of sedimentation rate in the outlet of Keduang sub-watershed, which was retrieved from the simulation in 2011-2014, was 408.19 tons/ha/year.